Cytotoxic effect of coscinium fenestratum on human head and neck cancer cell line (HN31) - Saranyapin Potikanond (2018)
© 2015 Saranyapin Potikanond et al. Coscinium fenestratum is widely used as a medicinal plant in many Asian countries. This study aimed to investigate the cytotoxic effect of a crude water extract of C. fenestratum (CF extract) compared to 5-fluorouracil (5-FU) on human HN31 cell line, a metastatic squamous cell carcinoma of the pharynx. The results revealed that cell morphology visualized under inverted light microscopy was changed from flat with a polygonal appearance to round appearance after CF extract application. The cell viability assay (MTT test) showed that the concentration producing 50% growth inhibition (IC at 48-hour incubation of CF extract on HN31 was 0.12 mg/mL, while the ICof 5-FU was 6.6 mg/mL, indicating that CF extract has a higher potency. However, combining various concentrations of 5-FU and CF extract at ICdid not show synergistic effect. The CF extract dose dependently increased cell apoptosis determined by Annexin-V and propidium iodide staining. It decreased the phosphorylation of p38 MAPK and pAkt, while it increased the tumor suppressor protein p53. In conclusion, the cytotoxicity of CF extract was associated with the modulation of p38 MAPK, pAkt, and p53 signal molecules, leading to inhibiting cell survival and increasing apoptosis. No synergistic effects of CF extract and 5-FU were observed.